Delineation of Homeostatic Immune Signatures Defining Viremic Non-progression in HIV-1 Infection - Singh, Amit Kumar; Salwe, Sukeshani; Padwal, Varsha; Velhal, Shilpa; Sutar, Jyoti; Bhowmick, Shilpa; Mukherjee, Srabani; Nagar, Vidya; Patil, Priya; Patel, Vainav (Frontiers in Immunology, 2020)
Viremic non-progressors (VNPs), a distinct group of HIV-1 infected individuals, exhibit no signs of disease progression and maintain persistently elevated CD4+ T cell counts for several years despite high viral replication. Comprehensive characterisation of homeostatic cellular immune signatures in VNPs can provide unique insights into mechanisms responsible for coping with viral pathogenesis as well as identifying strategies for immune restoration under clinically relevant settings such as anti-retroviral therapy (ART) failure. We report a novel homeostatic signature in VNPs which is preservation of the central memory CD4+ T cell (CD4+ TCM) compartment. In addition, CD4+ TCM preservation was supported by ongoing interleukin-7 (IL-7) mediated thymic repopulation of naïve CD4+ T cells leading to intact CD4+ T cell homeostasis in VNPs. Treg expansion was found to be a function of preserved CD4+ T cell count and CD4+ T cell activation independent of disease status. However, in the light of continual depletion of CD4+ T cell count in progressors but not in VNPs, Tregs appear to be involved in lack of disease progression despite high viremia. In addition to these homeostatic mechanisms resisting CD4+ T cell depletion in VNPs, a relative diminution of terminally differentiated effector subset was observed exclusively in these individuals that might ameliorate consequences of high viral replication. VNPs also shared signatures of impaired CD8+ T cell cytotoxic function with progressors evidenced by increased exhaustion (PD-1 upregulation) and CD127 (IL-7Rα) downregulation contributing to persistent viremia. Thus, the homeostatic immune signatures reported in our study suggest a complex multifactorial mechanism accounting for non-progression in VNPs.